Comparative Study Of Students Vocabulary Achievement Learnt Through Thematic Picture And Explanation Techniques In Smpn 22 Bandar Lampung - Yeni Susanti (LINGUISTIKA, 2010)
Vocabulary is one of language components in English. It has a very important role in communication. Rivers (1970) adds that it is impossible to learn a language without vocabulary. But in fact, based on the writers experience in the three-month-teaching training program in SMP Negeri 22 Bandar Lampung, the students generally have inadequate vocabulary. It is proven with their low score in every vocabulary exercise. Due to this lack of vocabulary, they often encounter difficulties, for example in reading their compulsory books. This statement is also supported by Murcia (1978) who said that some students claim that their primary problem in acquiring English is vocabulary. Clearly students lack of vocabulary should be immediately treated. Actually the students can learn all the words they need, without help, for example by looking for difficult words in dictionary. But the problem here is how the students are able to know the meaning of new words, remember the words and practice them in real situation. They still find difficulty in remembering words so that they become bored. To overcome the problem, a teacher should be able to find out ways of how to solve the problems that may appear while teaching-learning process is going on. Teacher should be able to choose proper technique and to select the materials which are relevant to the students condition, needs and age. Among many ways that can be applied in teaching vocabulary, the writer used thematic pictures and explanation.The objectives of this research are first, to know whether there is a significant different of a students vocabulary achievement between the students who are taught through thematic picture and through explanation and to see which one of the two techniques is more effective for teaching vocabulary at junior school. This quantitative research will be conducted at class VIII A and VIII B of SMPN 22 Bandar Lampung at the first semester. To collect the data, the researcher will administer pre test, treatment and post test.